1921
DOI: 10.1085/jgp.4.2.141
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Absorption of Potassium by Animal Cells

Abstract: 1. Frog muscles perfused with Ringer solution in which potassium chloride has been replaced by an equivalent amount of rubidium or cesium chloride take up rubidium or cesium and incorporate them into the tissue substance in such form as to be retained during a subsequent perfusion with potassium-free Ringer solution, provided the muscles contract during the first perfusion. Retention of rubidium or cesium by a resting muscle does not occur. 2. Rats on synthetic diets, adequate in all respects ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1927
1927
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The foregoing observations confirm and extend the earlier data which had indicated that rubidium and cesium could be taken up in large quantities by muscle cells (6)(7)(8)(9). They also confirm the previously reported fact that rubidium chloride lowers the blood CO2 content in alkalotic potassium-deficient rats (9) and extend the observations to demonstrate a similar, but less marked, acidifying effect of cesium chloride.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The foregoing observations confirm and extend the earlier data which had indicated that rubidium and cesium could be taken up in large quantities by muscle cells (6)(7)(8)(9). They also confirm the previously reported fact that rubidium chloride lowers the blood CO2 content in alkalotic potassium-deficient rats (9) and extend the observations to demonstrate a similar, but less marked, acidifying effect of cesium chloride.…”
Section: Discussionsupporting
confidence: 90%
“…2Presented in part at the Annual Meeting of the American Federation for Clinical Research, May, 1956. studies (6)(7)(8)(9) have already established in a general way that animal tissues are capable of accumulating significant quantities of rubidium or cesium, but there have been no determinations of the tissue-plasma concentration gradients when organisms are fed non-tracer amounts of these substances and no quantitative measurements of the extent to which these ions are taken up by tissues relative to potassium. The results of the present work indicate a distinctly greater affinity of rat muscle tissue for rubidium and cesium than for potassium, and the data therefore suggest that processes more complex than simple diffusion are involved in the normal accumulation of potassium.…”
mentioning
confidence: 99%
“…Since there is evidence that animal tissues can also accumulate large quantities of administered rubidium ions (9,16), it is reasonable to assume that the acidifying effects of rubidium in the present experiments were accomplished, at least in part, by a similar displacement of cellular hydrogen.…”
Section: Discussionmentioning
confidence: 78%
“…Although Rb is not considered extremely toxic it can exert toxic effects when in high concentrations, mainly because it competes with K for enzymes, such as the Na + /K + -ATPase (Meltzer, 1991;Mitchell et al, 1921). Accumulation of Rb has been observed in several organs of rats, and reported effects of this accumulation include spasms and tissue disorganization (Mitchell et al, 1921;Salaün and Truchet, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although Rb is not considered extremely toxic it can exert toxic effects when in high concentrations, mainly because it competes with K for enzymes, such as the Na + /K + -ATPase (Meltzer, 1991;Mitchell et al, 1921). Accumulation of Rb has been observed in several organs of rats, and reported effects of this accumulation include spasms and tissue disorganization (Mitchell et al, 1921;Salaün and Truchet, 1996). Strong and significant correlations found in donors from Furnas between Rb-Cd and Rb-Pb show that Rb hair concentrations may be used as biomarker of exposure to volcanic emissions, composed of more harmful gases and aerosols, as previously suggested by Durand et al (2004).…”
Section: Discussionmentioning
confidence: 99%